2013
DOI: 10.1007/s00134-013-3002-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement of interdisciplinary rounds by leadership training based on essential quality indicators of the Interdisciplinary Rounds Assessment Scale

Abstract: The leadership training improved the quality of the IDRs performed in the ICUs. This may improve quality and safety of patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Results of 99 patient discussions after training of leading skills training, guided and measured with the ten essential quality indicators, showed that this intervention was abletoimprovequalityofperformed IDRs in the ICUs. Furthermore, the sustained effect of the intervention, as measured at six weeks after the training, suggested that the training was still effective and useful for daily practice 8 .…”
Section: Remeasuring the Indices To Document Effects Post-test Of Thementioning
confidence: 98%
See 3 more Smart Citations
“…Results of 99 patient discussions after training of leading skills training, guided and measured with the ten essential quality indicators, showed that this intervention was abletoimprovequalityofperformed IDRs in the ICUs. Furthermore, the sustained effect of the intervention, as measured at six weeks after the training, suggested that the training was still effective and useful for daily practice 8 .…”
Section: Remeasuring the Indices To Document Effects Post-test Of Thementioning
confidence: 98%
“…Development of the IDR Assessment Scale, including the gold standard and a survey, was a starting point of several performance improvements for IDRs in multiple studies [6][7][8] . In this review, we discuss the application of these tools, and the potential for performance improvements in IDRs in general ICUs.…”
Section: Measuring Quality Of Team Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important finding of this study is that after implementation of morbidity and mortality conferences a change in organizational culture occurred over time: team-satisfaction-oriented culture took a leading role, whereas people-security oriented culture dramatically decreased. Ten Have et al [74] performed a nonrandomized study to assess whether leadership training could improve the quality of interdisciplinary rounds in four ICUs for adults in the Netherlands. The intervention consisted of a 1-day training session in a simulation environment and feedback sessions of videotaped behavior in the workplace.…”
Section: Safetymentioning
confidence: 99%